Pengaruh Variasi Produk, Fasilitas Dan Promosi Terhadap Kepuasan Pelanggan Di Baliku Jamur - Putu Elvina Clarissa; Ni Made Hartini; I Ketut Budiasa (Journal Research of Management, 2025)
Customer satisfaction is a very important factor that has an impact on a business, especially in the restaurant sector. This study aims to determine the effect of product variations, facilities and promotions on customer satisfaction at Baliku Jamur. This study applies a quantitative research method. The sampling technique used in this study is the purposive sampling research method. The sample in this study were Baliku Jamur customers who were 15 years old and over and had visited at least twice. The respondents of this study were 80 Baliku Jamur customers. The research analysis used multiple regression analysis using SPSS 25 For Windows. Data were collected using a questionnaire. The results of the analysis through multiple linear regression showed a regression model Y = 4.021 + 0.231X1 + 0.171X2 + 0.097X3. The results of the study indicate that product variation has a positive and significant effect on customer satisfaction at Baliku Jamur, as indicated by the positive regression coefficient b1X1. Facilities have a positive and significant effect on customer satisfaction at Baliku Jamur, as indicated by the positive regression coefficient b2X2. Promotion has a positive and significant effect on customer satisfaction at Baliku Jamur, as indicated by the positive regression coefficient b3X3. The suggestions from this study are to develop variations of processed mushroom products to strengthen the branding of Baliku Jamur, develop parking areas to improve visitor comfort, and optimize digital promotions through creative and interactive content on Instagram, TikTok, and Facebook to reach more customers.